Threshold effects of ICT access and usage in Burkinabe and Ghanaian households - Alhassan Abdul-Wakeel Karakara; Evans Osabuohien (African Governance and Development Institute (AGDI), 2021)
Information and communication technology (ICT) has a crucial role in the individual, businesses and cooperative lives of citizens. Many studies on ICT access tend to concentrate on the supply side of improving access to ICTs; however, limited efforts have been made to examine the households' demand side. Thus, this study contributes to the extant literature by investigating the demand side of ICT access by households. It also examines the socioeconomic characteristics that affect the households' access and usage of ICTs, which create a somewhat digital divide between 'ICT have' and 'have not' in Burkina Faso and Ghana. It employs Demographic and Health Survey (DHS) data for both Burkina Faso and Ghana 2014 in achieving its objectives. The results, among others, underscore different threshold effects in access to ICTs Burkinabe and Ghanaian households. Thus, to enhance the households' ICT access, and consequently, usage the features of the households should be taken into consideration when developing ICT access policies.
Keywords: O14; R22; 330; Burkina Faso; Ghana; Households; ICT access and Usage; Threshold effect